EFFECTIVENESS OF FLIPPED CLASSROOM IN MATHEMATICS TEACHING - Ramakrishnan; JohnsiPriya (International Journal of Research -GRANTHAALAYAH, 2016)
Flipped Classroom is an instructional strategy and a type of blended learning that reverses the traditional learning environment by delivering instructional content, often online, outside of the classroom. It moves activities, including those that may have traditionally been considered homework, into the classroom. In a flipped classroom, students watch online lectures, collaborate in online discussions, or carry out research at home and engage in concepts in the classroom with the guidance of a mentor. In traditional schools, each topic in class receives a fixed amount of time for all students. Flipped mastery classrooms apply a mastery learning model that requires each student to master a topic before moving to the next one. Flipped classroom will be most suitable for mathematics teaching as parents are not in a position to teach their wards on some mathematical problems working in the classroom with teacher will help them a lot. Hence, the investigators though of conducting an experiment study on Flipped classroom on mathematics teaching. The investigator being a mathematics teacher herself prepared a video lesson on Area and Perimeter one of the units in Mathematics subject of IX std. in Tamil Nadu state Board syllabus. The experiment was conducted in Govt. School in Chennai. The finding of the study reveals that flipped classroom has positively affected IX std. students’ achievement in mathematics.